Stress equations for adhesive in two-dimensional adhesively bonded joints = Równania naprężeń w płaskich dwuwymiarowych spoinach klejowych - Rapp, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of this paper is formulation of shear stress equations for plane two-dimensional adhesive layers present in adhesively bonded joints. The adherends are assumed to have the same thickness and be made of an isotropic material. The shape of theadherends in the joint plane is arbitrary.
Keywords: połączenie klejone; modele analityczne; dwuwymiarowa analiza naprężeń; izotropia; sprężystość liniowa; adhesively bonded joints; analytical models; two dimensional shear stresses; isotropy; linear elasticity